On (a,d)-antimagic labelings of Hn, FLn and mCn - Ramalakshmi Rajendran; K. M. Kathiresan (Indonesian Journal of Combinatorics, 2020)
In this paper, we derive the necessary condition for an (a,d )- antimagic labeling of some new classes of graphs such as Hn, F Ln and mCn. We prove that Hn is (7n +2, 1)-antimagic and mCn is ((mn+3)/2,1)- antimagic. Also we prove that F Ln has no ((n+1)/2,4)- antimagic labeling.